Prevalence of obsessive compulsive disorder among first year medical students in Sylhet division (Bangladesh Journal of Psychiatry, 2024)
Obsessive-compulsive disorder (OCD) is a chronic psychiatric disorder. High prevalence of emotional suffering and common mental disorders had been reported among medical students. The academic demands, increased responsibility, competition and lack of leisure time may lead to increased stress and anxiety. There is an immense scarcity of information about this common distressing and disabling disorder in Bangladeshi context. The objective of this study was to determine the prevalence of OCD among 1st year medical students in Sylhet division and find out other correlates. This was a cross sectional study done from 1st March 2022 to 31st January 2023 where 563 students were consecutively selected as sample; among which 546 retained as sample. A predesigned semi structured questionnaire, Obsessive-Compulsive Inventory - Revised (OCI-R), Yale-Brown Obsessive-Compulsive Scale Bangla (Y-BOCS); Depression, anxiety and stress scale 21 (DASS-21) and Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) were used as tools. The results showed that, majority of the participants were female, from government medical college, came from overprotective family and 42% of students never heard of OCD. Obsessive-compulsive symptoms (OCS) was present in 280 (51.28%) and OCD was present among 84 (15.38%) students. Seventy five percent of them had mild to moderate symptom severity. An independent samples t-test was used to compare the mean OCI R score across categorical variables. The t-test was statistically significant for family history of psychiatric illness and those with over protective family. OCS was significantly associated with anxiety, depression and stress and those with positive OCS had higher level of anxiety, depression and stress than those with negative OCS (22% versus 7%; 28% versus 9.2% and 10.4% versus 1.8%). In OCS subscale, ordering (n=51, 20.2%) was most common followed by obsessing (n=50, 19.8%), checking (n=24, 9.5%), hoarding (n=18, 7.1%), washing (n=12, 4.7%) and neutralizing (n=10, 4%). OCD was significantly associated with family history of psychiatric illness (÷2: 21.146; p